Synergistic mortality between a neonicotinoid insecticide and an ergosterol‐biosynthesis‐inhibiting fungicide in three bee species. Issue 6 (29th November 2016) - Sgolastra, Fabio; Medrzycki, Piotr; Bortolotti, Laura; Renzi, Maria Teresa; Tosi, Simone; Bogo, Gherardo; Teper, Dariusz; Porrini, Claudio; Molowny‐Horas, Roberto; Bosch, Jordi
Abstract: BACKGROUND: Neonicotinoid insecticides have been identified as an important factor contributing to bee diversity declines. Nonetheless, uncertainties remain about their impact under field conditions. Most studies have been conducted on Apis mellifera and tested single compounds. However, in agricultural environments, bees are often exposed to multiple pesticides. We explore the synergistic mortality between a neonicotinoid (clothianidin) and an ergosterol‐biosynthesis‐inhibiting fungicide (propiconazole) in three bee species ( A. mellifera, Bombus terrestris, Osmia bicornis ) following oral exposure in the laboratory. RESULTS: We developed a new approach based on the binomial proportion test to analyse synergistic interactions. We estimated uptake of clothianidin per foraging bout in honey bees foraging on seed‐coated rapeseed fields. We found significant synergistic mortality in all three bee species exposed to non‐lethal doses of propiconazole and their respective LD10 of clothianidin. Significant synergism was only found at the first assessment times in A. mellifera (4 and 24 h) and B. terrestris (4 h), but persisted throughout the experiment (96 h) in O. bicornis . O. bicornis was also the most sensitive species to clothianidin. CONCLUSION: Our results underscore the importance to test pesticide combinations likely to occur in agricultural environments, and to include several bee species in environmental risk assessment schemes. © 2016 Society of Chemical Industry